Catalytic enantioselective acyl transfer: the case for 4-PPY with a C-3 carboxamide peptide auxiliary based on synthesis and modelling studies. Issue 46 (4th November 2016) - Cozett, Rudy E.; Venter, Gerhard A.; Gokada, Maheswara Rao; Hunter, Roger
Abstract : A scalable, chiral peptide-based 4-PPY enantioselective acyl transfer catalyst has been developed using computer modelling. Abstract : A series of 4-pyrrolidinopyridine (4-PPY) C-3 carboxamides containing peptide-based side chains have been synthesised and evaluated in the kinetic resolution of a small library of chiral benzylic secondary alcohols. A key design element was the incorporation of a tryptophan residue in the peptide side chain for promoting π-stacking between peptide side chain and the pyridinium ring of the N -acyl intermediate, in which modelling was used as a structure-based guiding tool. Together, a catalyst containing a LeuTrp- N -Boc side chain (catalyst8 ) was identified that achieved s -values up to and in slight excess of 10. A transition-state model based on the modelling is proposed to explain the origin of enantioselectivity. This study establishes the usefulness of modelling as a structure-based guiding tool for enantioselectivity optimization as well as the potential for developing scalable peptide-based DMAP-type catalysts for large-scale resolution work.